2016
DOI: 10.1097/eja.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative dexmedetomidine reduces early postoperative nausea but not vomiting in adult patients after gynaecological laparoscopic surgery

Abstract: Chinese Clinical Trial Registry ChiCTR-IPR-15006914.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…As an adjuvant to general anesthesia, dexmedetomidine provides additional benefits of reducing the dose of inhalation agent and opioid analgesics [910], improving the quality of recovery, decreasing postoperative nausea and vomiting [911], and enhancing postoperative gastrointestinal motility [12]. Gupta et al [7] also show that dexmedetomidine infusion allows significant reductions in the amounts of isoflurane and intraoperative fentanyl required, while maintaining the targeted blood pressure.…”
mentioning
confidence: 99%
“…As an adjuvant to general anesthesia, dexmedetomidine provides additional benefits of reducing the dose of inhalation agent and opioid analgesics [910], improving the quality of recovery, decreasing postoperative nausea and vomiting [911], and enhancing postoperative gastrointestinal motility [12]. Gupta et al [7] also show that dexmedetomidine infusion allows significant reductions in the amounts of isoflurane and intraoperative fentanyl required, while maintaining the targeted blood pressure.…”
mentioning
confidence: 99%
“…We used the methodology previously described by our recent study [8].Participant screening was performed the day before surgery. The inclusion criteria were: (1) female patients; (2) Neo-adjuvant chemoradiotherapy before surgery, (9) alcoholism or drug abuse, (10) any regimen of antiemetic, glucocorticoids or psychotropic drugs which are known to have an influence on the occurrence of PONV within 24h before surgery.…”
Section: Participants Selectionmentioning
confidence: 99%
“…Study sample size was calculated according to our previous studies [3,8],we estimated an incidence of PONV of 50% in the control group for this patient population. A sample size of 55 patients in each group was needed to detect a 50% reduction in the incidence of PONV (from 50 to 25%) with a power of 80% and a two-sided α error of 0.05.…”
Section: Samplesize Calculationmentioning
confidence: 99%
“…We used the methodology previously described by our recent study [8]. Participant screening was performed the day before surgery.…”
Section: Participants Selectionmentioning
confidence: 99%
“…In our previous study, we demonstrated that intraoperative supplemental use of dexmedetomidine resulted in a lower incidence of nausea during the first 2 h postoperatively for patients undergoing gynecological laparoscopic surgery [8]. Other studies about susceptible patients who underwent gynecological laparoscopic surgery were also focused on the intraoperative use of dexmedetomidine other than adding dexmedetomidine to patient-controlled analgesia (PCA) regimen [9][10][11][12].…”
mentioning
confidence: 99%